Off-shell supersymmetry versus hermiticity in superstrings - Berkovits, Nathan [UNESP] (American Physical Society (APS), 1996)
We point out that off-shell four-dimensional spacetime supersymmetry implies strange Hermiticity properties for the N = 1 Ramond-Neveu-Schwarz superstring. However, these Hermiticity properties become natural when the N = 1 superstring is embedded into an N = 2 superstring.